EPENDYMAL AND PERIVENTRICULAR MAGNETIC RESONANCE IMAGING CHANGES IN FOUR DOGS WITH CENTRAL NERVOUS SYSTEM BLASTOMYCOSIS. Issue 5 (13th May 2013) - Bentley, R. Timothy; Reese, Michael J.; Heng, Hock Gan; Lin, Tsang Long; Shimonohara, Nozomi; Fauber, Amy
Abstract : Rapid detection of central nervous system (CNS) involvement is important for dogs with blastomycosis, as this can affect antifungal drug selection and has been associated with an increased risk of death. Previous reports describing magnetic resonance imaging (MRI) characteristics of canine CNS blastomycosis primarily identified mass lesions. The purpose of this retrospective study was to determine whether other MRI characteristics of CNS blastomycosis may also occur. Medical records of the Purdue University Veterinary Teaching Hospital were searched and four dogs met inclusion criteria. Magnetic resonance imaging characteristics included periventricular edema, periventricular and meningeal contrast enhancement, and ventriculomegaly. Periventricular lesions most commonly involved the rostral horn of the lateral ventricles and the third ventricle. Increased meningeal contrast enhancement involved the cerebrum, thalamus, sella turcica, and brainstem. Findings indicated that, in addition to mass lesions, MRI characteristics of periventricular hyperintensity, contrast enhancement, and ventriculomegaly may also occur in dogs with CNS blastomycosis.